2021
DOI: 10.1038/s41430-020-00848-4
|View full text |Cite
|
Sign up to set email alerts
|

Malnutrition screening on hospital admission: impact of overweight and obesity on comparative performance of MUST and PG-SGA SF

Abstract: Background/objectives Traditional malnutrition screening instruments, including the Malnutrition Universal Screening Tool (MUST), strongly rely on low body mass index (BMI) and weight loss. In overweight/obese patients, this may result in underdetection of malnutrition risk. Alternative instruments, like the Patient-Generated Subjective Global Assessment Short Form (PG-SGA SF), include characteristics and risk factors irrespective of BMI. Therefore, we aimed to compare performance of MUST and PG-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
18
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 33 publications
(23 citation statements)
references
References 57 publications
3
18
1
1
Order By: Relevance
“…This indicates a higher prevalence of risk factors for malnutrition in patients admitted to medical wards, consistent with a previous multi-center study on Internal Medicine wards [43]. Our previous cross-sectional analysis of the current cohort, moreover, indicates that BMI is a major factor affecting differences in diagnostic properties of MUST as compared to PG-SGA SF, with the most pronounced difference in patients with an overweight or obese BMI [28]. This may be of particular and increasing relevance, in an ageing and increasingly obese society [44].…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…This indicates a higher prevalence of risk factors for malnutrition in patients admitted to medical wards, consistent with a previous multi-center study on Internal Medicine wards [43]. Our previous cross-sectional analysis of the current cohort, moreover, indicates that BMI is a major factor affecting differences in diagnostic properties of MUST as compared to PG-SGA SF, with the most pronounced difference in patients with an overweight or obese BMI [28]. This may be of particular and increasing relevance, in an ageing and increasingly obese society [44].…”
Section: Discussionsupporting
confidence: 90%
“…Observational studies in hospital patients and patients with chronic kidney disease have previously shown that the PG-SGA SF identifies a considerably larger percentage of patients at risk compared with the MUST [25e27]. This is consistent with a recent cross-sectional analysis from our hospital, in which we found an approximately 2.5-fold higher percentage of patients at risk according to the PG-SGA SF, compared with MUST [28]. However, whether this difference in classification, particularly the larger yield of the PG-SGA SF, has important clinical consequences, i.e., whether it also translates into corresponding higher risk of worse outcomes, has yet to be investigated.…”
Section: Introductionsupporting
confidence: 92%
See 1 more Smart Citation
“…Grupo total Idosas Adultas ...continuação -Tabela 3 não é recomendado para avaliar desnutrição em oncologia, uma vez que não consegue diferenciar com precisão os componentes do peso corporal, podendo mascarar a perda de massa magra em pessoas com IMC dentro da faixa saudável ou com excesso de peso 21,22 . O que torna importante a utilização de outros métodos de avaliação como a ASG-PPP que possui maior sensibilidade em pacientes com câncer 23,24 .…”
Section: Faixa Etáriaunclassified
“…The following questionnaires will be administered: Six-Dimensional EuroQol Instrument (EQ-6D) [ 49 ] and the Short Form 36 Health Survey (SF36) [ 50 ] to assess HRQoL; Checklist Individual Strength (CIS) [ 51 ] to assess fatigue; Dialysis Symptom Indicator (DSI) [ 16 ] to assess the prevalence, severity, and impact of symptoms in hemodialysis patients; Groninger Frailty Indicator (GFI) [ 52 ] to identify frailty; Cognitive Failure Questionnaire (CFQ) [ 53 ] to assess cognitive failure; Patient Health Questionnaire-9 (PHQ-9) [ 54 ] to measure depressive disorders and depression severity; and the Patient-Generated Subjective Global Assessment (PG-SGA) [ 55 , 56 , 57 ] to assess nutritional status. Patients can fill in the questionnaires at home before the start of the hemodialysis session, or during the dialysis session with the help of a researcher.…”
Section: A Clinical Pilot Studymentioning
confidence: 99%